Analisis Yuridis Pembatalan Perjanjian Jual Beli Tanah Akibat Adanya Cacat Kehendak Ditinjau dari Pasal 1321 KUH Perdata: Studi Kasus Putusan Pengadilan Negeri Blitar Nomor 34/Pdt.G/2024/Pn Blt - Via Fariha Risfi Al Hadist (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the determination of defects of consent in land sale and purchase agreements based on Article 1321 of the Civil Code through a study of the Blitar District Court Decision No. 34/Pdt.G/2024/PN Blt. The study employs a normative legal method using both a statutory and a case-based approach. This study addresses this research gap by examining the Decision of the Blitar District Court Number 34/Pdt.G/2024/PN BLT using causation theory, presumption theory and relevance theory. The research focuses on determining the existence of defects of consent and their legal consequences for land sale and purchase agreements. The findings indicate that the court did not thoroughly assess the elements of defects of consent, placing greater emphasis on proving land ownership rights than on the causal relationship between defects of consent and the annulment of the agreement. As a result, the causal relationship between the existence of a defect of consent and the rescission of a land sale agreement has not been explicitly analyzed, so the legal basis for rescission under Article 1321 of the Civil Code has not been fully applied.